Edukasi Keselamatan Air: Mengenal Risiko Tenggelam dan Penanganannya di SMP Muhammadiyah 1 Samarinda - Rumba, Divha Rizdyawati; Fitriana, Winda; Pinky, Rizkia Syalis; Rheisya, Salbina; Safrudin, M. Bachtiar (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Drowning victims need to be treated right away since they constitute an emergency. Because of the rescue system's and early treatment elements' contributions, the drowning death rate remains high. This is probably caused by the public's poor comprehension of emergency circumstances and improper knowledge on how to handle sufferers. This study aims to increase our understanding of First Aid for Drowning Victims. By gathering library data, reviewing and taking notes, and organizing research materials, this kind of study is a literature review. Increased public awareness of first aid from reliable sources, including medical professionals, about first aid procedures for drowning victims can help combat the drowning problem. The literature study method was employed to gather this data. Seeking assistance, pulling the drowning victim out of the water, monitoring their respiration, administering manual cardiopulmonary resuscitation, and warming their body are some of the first aid techniques that can be used.